Conserving migratory waterbirds and the coastal zone: the future of South-east Asia's intertidal wetlands. Issue 2 (21st March 2022) - Yong, Ding Li; Kee, Jing Ying; Aung, Pyae Phyo; Jain, Anuj; Yeap, Chin-Aik; Au, Nyat Jun; Jearwattanakanok, Ayuwat; Lim, Kim Keang; Yu, Yat-Tung; Fu, Vivian W. K.; Insua-Cao, Paul; Sawa, Yusuke; et al.
Abstract: South-east Asia's diverse coastal wetlands, which span natural mudflats and mangroves to man-made salt pans, offer critical habitat for many migratory waterbird species in the East Asian–Australasian Flyway. Species dependent on these wetlands include nearly the entire population of the Critically Endangered spoon-billed sandpiper Calidris pygmaea and the Endangered spotted greenshank Tringa guttifer, and significant populations of several other globally threatened and declining species. Presently, more than 50 coastal Important Bird and Biodiversity Areas (IBAs) in the region (7.4% of all South-east Asian IBAs) support at least one threatened migratory species. However, recent studies continue to reveal major knowledge gaps on the distribution of migratory waterbirds and important wetland sites along South-east Asia's vast coastline, including undiscovered and potential IBAs. Alongside this, there are critical gaps in the representation of coastal wetlands across the protected area networks of many countries in this region (e.g. Viet Nam, Indonesia, Malaysia), hindering effective conservation. Although a better understanding of the value of coastal wetlands to people and their importance to migratory species is necessary, governments and other stakeholders need to do more to strengthen the conservation of these ecosystems by improving protected area coverage, habitat restoration, and coastal governance and management. This must be underpinned by the judicious use of evidence-based approaches, including satellite-tracking of migratory birds, ecological research and ground surveys.